Dynamically Tunable Friction via Subsurface Stiffness Modulation - Sharifi, Siavash; Rux, Caleb; Sparling, Nathaniel; Wan, Guangchao; Mohammadi Nasab, Amir; Siddaiah, Arpith; Menezes, Pradeep; Zhang, Teng; Shan, Wanliang (Frontiers in Robotics and AI, 2021)
Currently soft robots primarily rely on pneumatics and geometrical asymmetry to achieve locomotion, which limits their working range, versatility, and other untethered functionalities. In this paper, we introduce a novel approach to achieve locomotion for soft robots through dynamically tunable friction to address these challenges, which is achieved by subsurface stiffness modulation of a stimuli-responsive component within composite structures. To demonstrate this, we design and fabricate an elastomeric pad made of polydimethylsiloxane (PDMS), which is embedded with a spiral channel filled with a low melting point alloy (LMPA). Once the LMPA strip is melted upon Joule heating, the compliance of the composite structure increases and the friction between the composite surface and the opposing surface increases. A series of experiments and finite element analysis (FEA) have been performed to characterize the frictional behavior of these composite pads and undercover the underlying physics dominating the tunable friction. We also demonstrate that, when these composite structures are properly integrated to soft crawling robots inspired by inchworms and earthworms, the differences in friction of the two ends through subsurface stiffness modulation can potentially be used to generate translational locomotion for untethered crawling robots.